(untitled) (Bangladesh Journal of Botany, 2021)
The ethanolic extracts of different parts of Anisophyllea disticha were tested for antimicrobial capability using disc diffusion assay. The result revealed positive growth inhibitory activity, but was considered weak for all extracts against Gram positive bacteria. Leaf extract displayed the highest zone of inhibition with values of 10.67 ± 0.58 and 8.67 ± 0.58 mm against Staphylococcus epidermidis and S. aureus, respectively. On the other hand, stem showed the highest amount of total phenolic content (TPC) (27.73 ± 4.10 mg GAE/g extract) and similar trend was also observed in antioxidant potential in terms of DPPH radical scavenging activity (66.20 ± 11.74%) and ferric reducing antioxidant power assay (FRAP) (203.63 ± 16.03 mg Fe(II)/g extract). High positive correlation was found between TPC and antioxidant activities, suggesting that phenolic compounds contribute to the antioxidant power of plant extracts. HPLC analysis identified and quantified gallic acid, p-coumaric, ferulic acid and quercetin in the extracts. Bangladesh J. Bot. 50(3): 515-521, 2021 (September)